2015
DOI: 10.1155/2015/307453
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Relevance of IL-17-Producing CD4+CD161+ Cell and Its Subpopulations in Primary Sjögren’s Syndrome

Abstract: Objective. Th17 cells have been demonstrated to play an important role in the onset and development of primary Sjögren's syndrome (pSS). In this study, we evaluated the expansion and clinical significance of circulating CD4+CD161+ T cell and its “effector” (CD4+CD25−CD161+ T cell) and “regulatory” (CD4+CD25+CD161+ T cell) subpopulations. Methods. Fifty-eight pSS patients and 16 healthy controls (HCs) were recruited in our study. The cell populations and intracellular IL-17 expression were analyzed by flow cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 46 publications
(54 reference statements)
0
19
0
2
Order By: Relevance
“…Recently, it has been reported that an IL-17-producing CD161 + CD25 − CD4 + T-cell subpopulation as effector cells and a CD161 + CD25 + CD4 + T-cell subpopulation as regulatory cells in peripheral blood mononuclear cells (PBMCs) from SS patients are related to the clinical severity of the pathogenesis of SS [ 111 ]. Compared with healthy controls, a significant increase in the number of CD161 + CD25 + CD4 + T cells was also observed in PBMCs from SS patients [ 111 ]. In addition, the function of this unique regulatory cell population in SS patients is more impaired than that of CD161 − CD25 + CD4 + T reg cells [ 111 ].…”
Section: Treg Cells In Ssmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been reported that an IL-17-producing CD161 + CD25 − CD4 + T-cell subpopulation as effector cells and a CD161 + CD25 + CD4 + T-cell subpopulation as regulatory cells in peripheral blood mononuclear cells (PBMCs) from SS patients are related to the clinical severity of the pathogenesis of SS [ 111 ]. Compared with healthy controls, a significant increase in the number of CD161 + CD25 + CD4 + T cells was also observed in PBMCs from SS patients [ 111 ]. In addition, the function of this unique regulatory cell population in SS patients is more impaired than that of CD161 − CD25 + CD4 + T reg cells [ 111 ].…”
Section: Treg Cells In Ssmentioning
confidence: 99%
“…Compared with healthy controls, a significant increase in the number of CD161 + CD25 + CD4 + T cells was also observed in PBMCs from SS patients [ 111 ]. In addition, the function of this unique regulatory cell population in SS patients is more impaired than that of CD161 − CD25 + CD4 + T reg cells [ 111 ].…”
Section: Treg Cells In Ssmentioning
confidence: 99%
“…The prevalence of CD4+ T cells decreases with lesion severity, whereas the prevalence of CD8+ T cells remains unchanged [ 9 , 10 ]. More recently, the involvement of Th17 lymphocytes was detected, with a key role in inflammation, autoimmunity, and glandular tissue damage in SS [ 11 ]. Th17 cells, in association with Th1 and Th2 cells, are responsible for increased inflammatory cytokine production, such as IL-21 and IL-22 [ 12 ] which have been found in high concentration in the serum and salivary glands of SS patients [ 13 , 14 ] with high relation to clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Th17 cells, in association with Th1 and Th2 cells, are responsible for increased inflammatory cytokine production, such as IL-21 and IL-22 [ 12 ] which have been found in high concentration in the serum and salivary glands of SS patients [ 13 , 14 ] with high relation to clinical symptoms. Moreover, matrix (interleukin) IL-17, transforming growth factor β (TGF- β ), IL-6, and metalloproteinase (MMP) [ 11 ] are also expressed hypothesizing their involvement in the development and the onset of SS through the modulation of target tissue homeostasis and biological activities [ 13 ]. In mononuclear cells, infiltration has found also natural killer (NK) cells and professional antigen-presenting cells, such as macrophages and dendritic cells, and a small, but considerable, portion of the infiltrating mononuclear cells, and their percentage correlates with the grade of the lesions [ 9 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Увеличение концентрации ИЛ22 в сыворотках больных СШ коррелирует с выраженностью ксеросто-мии, увеличением концентрации ревматоидного фактора (РФ), анти-SSB-антител и гипергаммаглобулинемией [126]. В периферической крови пациентов с СШ отмеча-ется увеличение субпопуляции Th17-клеток (CD4+CD161+), ассоциирующееся с активностью (ин-декс ESSDAI ≥4), лабораторными параметрами (СОЭ, гипергаммаглобулинемия, тромбоцитопения, анти-SSB) и тяжестью заболевания [127] Фармакотерапия ИЛ17-ассоциированных иммуновоспалительных заболеваний: фокус на секукинумаб Впервые терапевтическая эффективность ингибиции Th17-клеток и синтеза ИЛ17 при ИВЗ человека была про-демонстрирована у пациентов с псориазом, получавших лечение препаратом устекинумаб, который представляет собой мАТ к ИЛ12/ИЛ23 [128]. Однако, поскольку эти ан-титела ингибируют не только Th17-, но и Th1-тип иммун-ного ответа, клиническое значение подавления активации именно Th17 оставалось не доказанным.…”
Section: синдром шегренаunclassified